Developing Communication Model of Creative Gen-Z Employees for Effective Communication Across Generations: A Case Study of Infia Corporation - Hartaman Karnaen, Muhammad Akbar; Pratama, Andika Putra (Journal of Economics and Business UBS, 2025)
This research explores the communication dynamics at Infia Corporation, a fast-growing creative industry company in Indonesia, where Generation Z form a significant part of the workforce. The research identified key challenges in communication between Generation Z employees and older generations, such as Millennials and Generation X's. This communication gap is caused by differences in communication styles, technological tools being utilized, as well as feedback mechanisms. This research proposes the implementation of a hybrid communication model that combines formal and informal communication channels to accommodate the diverse preferences between generations within the organization. This study utilized a qualitative approach, which is a combination of descriptive and exploratory research. In addition, intergenerational bonding programs, two-way feedback systems, standardized language guidelines, and structured integration of communication technologies are also suggested as solutions to bridge the differences between generations. The findings of this research are expected to help Infia Corporation improve internal communication, create a more inclusive and collaborative work environment, and improve overall organizational performance. This research aims to create a communication framework that ensures effective interaction between employees from different generational backgrounds, while staying aligned with the creative and innovative corporate culture.